Lower abdominal adipose tissue cannabinoid type 1 receptor availability in young men with overweight - Pekkarinen L.; Kantonen T.; Oikonen V.; Haaparanta-Solin M.; Aarnio R.; Dickens A.M.; von Eyken A.; Latva-Rasku A.; Dadson P.; Kirjavainen A.K.; Rajander J.; Kalliokoski K.; et al. (John Wiley and Sons Inc, 2025)
Objective
Cannabinoid type 1 receptors (CB1R) modulate feeding behavior and energy homeostasis, and the CB1R tone is dysgulated in obesity. This study aimed to investigate CB1R availability in peripheral tissue and brain in young men with overweight versus lean men.
Methods
Healthy males with high (HR, n = 16) or low (LR, n = 20) obesity risk were studied with fluoride 18–labeled FMPEP-d2 positron emission tomography to quantify CB1R availability in abdominal adipose tissue, brown adipose tissue, muscle, and brain. Obesity risk was assessed by BMI, physical exercise habits, and familial obesity risk, including parental overweight, obesity, and type 2 diabetes. To assess insulin sensitivity, fluoro-[18F]-deoxy-2-D-glucose positron emission tomography during hyperinsulinemic-euglycemic clamp was performed. Serum endocannabinoids were analyzed.
Results
CB1R availability in abdominal adipose tissue was lower in the HR than in the LR group, whereas no difference was found in other tissues. CB1R availability of abdominal adipose tissue and brain correlated positively with insulin sensitivity and negatively with unfavorable lipid profile, BMI, body adiposity, and inflammatory markers. Serum arachidonoyl glycerol concentration was associated with lower CB1R availability of the whole brain, unfavorable lipid profile, and higher serum inflammatory markers.
Conclusions
The results suggest endocannabinoid dysregulation already in the preobesity state.